O avesso do contemporâneo: a expressão de um tempo na obra Olhos d'água, de Conceição Evaristo - Oliveira, Gleidson Ferreira de (2024)
Contemporaneity is a time that moves backwards, reflecting its yearnings in the literature it produces. Therefore, we propose in this work to think about the relationship between literature and the time in which it is inserted, taking as an exponent the short stories “Olhos d'água”, “Maria” and “A gente combinamos de não morrer”, present in Conceição Evaristo's collection “Olhos d'água”. Our research focuses on seeking arguments that point to the presence of themes that dialog with the current reader in the author's texts, based on Giorgio Agamben's definition of contemporary. The work is developed taking as its prerogatives the social and political mutations suffered in Brazil and the world during the mid-twentieth century, generated in part by globalization and mediatization, due to the so-called culture war, relating these issues to Evaristo's literary recognition in recent years. To do this, we will use three categories associated with social cultural debates as a basis: autofictional literature, political (or engaged) literature, and the concept of collectivity in literature. To do this, in the first category, we will take as a guide the perspective proposed by researcher Leyla Perrone-Moisés (2018) and Stuart Hall (2020); in the second category, we will use the ideas of Gayatri Chakravorty Spivak (2010); and in the third category, we will use the very notion of the collective, a fundamental component for the idea of thinking about the whole, present in the concept of “Writing-living”, proposed by Evaristo. We believe that these categories, present in the author’s works, reinforce her relevance for contemporary Brazilian literature.